Complete Serological Profile and Diagnostic Correctness of Celiac Disease Immunological markers in a Pediatric Population - Kadhium, Noora M. (American Journal of Biology and Natural Sciences, 2026)
Background: Celiac disease (CD) is consider an autoimmune disease which can be initiated by gluten intake,which need an accurate serological testing and supervision. Many different antibody tests are accessible, but the ideal cut-offs and combination of tests in pediatric patients require more details explanation. Objective: To determine the diagnostic efficiency of multiple antibody used to diagnose celiac disease, determine ideal cut-off measures, and evalute the effect of gluten-free diet (GFD) compiance on immunological markers in children and teenagers. Methods: analysis of the present study we take 180 patients (ages 2-18 years) with documented demographic information, family history, and serum antibody which markers including total IgA, tTG-IgG, tTG-IgA, DGP-IgG, DGP-IgA, EMA-IgG, and EMA IgA. Statistical analyses was done by using SPSS software and the tests included logistic regression, ROC analysis correlation analysis and t-tests. Results: Patients who have not following GFD (n=54) revealed significantly higher serum antibody titers compared to those on GFD (n=126): tTG-IgA (58.4±28.1 vs 8.7±10.2, p<0.001), EMA IgA (62.3±18.9 vs 9.2±8.4, p<0.001). tTG-IgA showed powerful diagnostic functioning (AUC=0.94), with ideal cut-off ≥20 U/mL with 92% specificity and 88% sensitivity. Logistic regression analysis recognized that tTG-IgA (OR=1.20, 95% CI:1.13-1.27) and EMA IgA (OR=1.16, 95% CI:1.07-1.26) as significant indicators. Children (2-9 years old) had significantly higher antibody values when compared to teenagers (10-17 years old). Conclusions: tTG-IgA ≥20 U/mL showed perfect diagnostic efficacy for patients without treatment. Positive correlations between antibody measures suggest excessive testing could be lowered. Age-related reference ranges may inhance diagnostic correctness in pediatric patients.